The Experimental Investigation of the Optimization of the Flow State of a Ladder-Shaped Spillway in a Certain Reservoir. (3rd March 2022) - Gu, Xin-Bao; Zhang, Yang; Wu, Qi-Hong; Wang, Yong
Abstract : The original design scheme of ladder-shaped spillways in certain reservoirs is improved by using a hydraulic similar model experiment. The results of the original scheme demonstrate that the stilling basin cannot meet the requirement of safe discharge, and the flow state at the end of the stilling basin is violent and chaotic. The experimental method of the physical model was used to optimize the design of the spillway without changing the original plane layout. First, three steps in the ladder are added. The stilling basin is then replaced by the torsion plane. Finally, the longitudinal slope of the tail channel section is altered, and an experimental investigation on the flow state and energy dissipation rate is performed. The conclusions are drawn that the flow state of the water is obviously improved, and the energy dissipation rate increases; the optimal scheme produces the expected effects.